Lee Yu-Hwa, Fantasy and Realism in Chinese Fiction; Tang Love Themes in Contrast, San Francisco, Chinese Materials Center Publications, 1984 (Asian Library Series, núm. 38), pp. xii + 89. - Maeth Ch., Russell (Estudios de Asia y África, 1986)
-